Hydrostatic pressure tuned magneto-structural transition and occurrence of pressure induced exchange bias effect in Mn0.85Fe0.15NiGe alloy. (24th August 2016) - Dutta, P; Pramanick, S; Das, D; Chatterjee, S
Abstract: The magnetic and magneto-functional behavior of a Fe-doped MnNiGe alloy with nominal composition Mn0.85 Fe0.15 NiGe have been investigated in ambient as well as in high pressure conditions. The alloy undergoes a first order martensitic phase transition (MPT) around 200 K and also shows a large conventional magnetocaloric effect (MCE) ( Δ S ∼ − 21 J kg −1 K −1 for magnetic field ( H ) changing from 0–50 kOe) around the transition in ambient conditions. The application of external hydrostatic pressure ( P ) results in a shift in MPT towards the lower temperature and a clear decrease in the saturation moment of the alloy at 5 K. The peak value of MCE is also found to decrease with increasing external P (∼18 J kg −1 K −1 decrease in Δ S has been observed for P = 12.5 kbar). The most interesting observation is the occurrence of the exchange bias effect (EBE) on application of external P . The competing ferromagnetic and antiferromagnetic interaction in the presence of external P plays the pivotal role towards the observation of P induced EBE.